Preparation method of alkali activator activated fiber reinforced steel slag concrete

By leveraging the synergistic effect of composite alkaline activators, hybrid fibers, and multi-source industrial solid waste aggregates, the problems of slow early strength development and insufficient toughness in steel slag concrete have been solved, achieving efficient resource utilization and performance improvement of steel slag concrete.

CN121672980APending Publication Date: 2026-03-17SHAANXI RAILWAY INST
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202610171699.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-02-06
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing technologies struggle to fully activate steel slag while simultaneously improving its early strength and fracture toughness, and to achieve efficient and synergistic resource utilization of various industrial solid wastes, thus limiting the practical application of steel slag concrete in engineering projects.

Method used

A concrete preparation method employing the synergistic effect of composite alkaline activator, hybrid fiber, and multi-source industrial solid waste aggregate is proposed. By constructing a concrete system with the synergistic effect of composite alkaline activator, hybrid fiber, and multi-source industrial solid waste aggregate, the potential cementitious activity of steel slag is enhanced, a dense CSH gel is generated, and the fiber-matrix interface bonding strength is strengthened. The aggregate gradation is optimized to achieve multi-scale toughening.

Benefits of technology

It significantly improves the early strength and fracture toughness of steel slag concrete, realizes the efficient resource utilization of various industrial solid wastes, and takes into account both mechanical properties and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121672980A_ABST
    Figure CN121672980A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, particularly relates to a preparation method of alkali activator activated fiber reinforced steel slag concrete, and aims to solve the problems that the steel slag concrete is low in early strength, insufficient in toughness and low in industrial solid waste synergistic utilization rate. According to the preparation method disclosed by the invention, a multi-source aggregate system is formed by the hot disintegration treated steel slag, the recycled coarse aggregate, the tailing sand and the natural sand; sodium silicate with the modulus of 1.0-1.5 and sodium carbonate / sodium hydroxide mixed alkali form a composite alkali activator; 1.0%-1.5% of corrugated steel fibers and 0.4%-0.6% of bunchy polypropylene fibers are doped to form a hybrid reinforcing system; the concrete is prepared through aggregate pre-wetting, staged stirring and a standard curing process. According to the method, the early strength and the fracture toughness can be remarkably improved, and efficient resource utilization of various industrial solid wastes is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building materials technology, and specifically relates to a method for preparing fiber-reinforced steel slag concrete activated by an alkaline activator. Background Technology

[0002] The high-value utilization of industrial solid waste in civil engineering materials has become an important development direction in the field of building materials. Steel slag, as a major by-product of iron and steel smelting, has a huge annual output. Its physical and chemical properties are similar to those of natural aggregates, and theoretically it has the potential to replace some cement or aggregates in concrete preparation. However, in practical engineering applications, steel slag concrete has long been limited by three core bottlenecks: First, the low pozzolanic activity of steel slag itself leads to slow hydration reaction and severely delayed early strength development. Typically, the 7-day compressive strength can only reach 30% to 40% of the 28-day strength, which is difficult to meet the requirements of modern engineering for rapid formwork removal and early load-bearing capacity. Second, the steel slag concrete matrix is ​​significantly brittle and lacks an effective energy dissipation mechanism during stress, making it prone to sudden brittle failure, which limits its promotion in high-toughness scenarios such as earthquake resistance and impact resistance. Third, current solid waste utilization models are mostly single-component substitutions, and there is a lack of systematic collaborative design among diverse industrial solid wastes such as steel slag, tailings sand, and recycled aggregates, resulting in low resource utilization efficiency and failure to form an integrated effect of complementary performance and structural optimization.

[0003] To address the aforementioned issues, existing technological approaches primarily explore two directions. On one hand, researchers attempt to introduce alkaline activator systems, such as water glass and sodium hydroxide, to accelerate the dissolution and repolymerization of the silica-alumina phase in steel slag by increasing the pH of the pore fluid. This promotes the formation of cementitious products (such as CSH gel), effectively enhancing later-stage strength and improving microstructural density. While this method alleviates the problem of insufficient steel slag activity to some extent, its mechanism of action focuses on strengthening the chemical reactions within the matrix, contributing little to the toughness indicators in macroscopic mechanical behavior. Furthermore, the increased alkalinity may even exacerbate the concentrated initiation of microcracks. On the other hand, fiber reinforcement technology is widely used to improve the fracture toughness and crack resistance of concrete. Steel fibers or polypropylene fibers are commonly used to delay structural failure by bridging cracks and absorbing fracture energy. However, in steel slag concrete systems, due to factors such as insufficient surface roughness of steel slag, strong chemical inertness, and the complex interfacial microenvironment after the introduction of activators, the interfacial bond strength between fibers and the matrix is ​​generally low. The measured value is usually only 60% to 70% of the matrix's own strength, which seriously weakens the toughening effect of fibers and leads to the frequent occurrence of the phenomenon of "fiber addition without toughening".

[0004] At a deeper level, while the two aforementioned technical approaches have each made local progress in specific dimensions, they are trapped in a performance fragmentation due to a lack of systematic understanding of the coupling mechanism of "activation-reinforcement-gradation". Specifically, although alkaline activators can activate steel slag to generate more cementitious phases, if the physicochemical compatibility of the fiber-matrix interface is not optimized simultaneously, the newly formed gel will be difficult to effectively anchor the fiber surface. Conversely, even if hybrid fibers are introduced to achieve multi-scale toughening, if the aggregate gradation is unreasonable and the pore structure is not fully filled, the spatial constraint effect of the activation reaction and the uniformity of fiber distribution will be greatly reduced. Crucially, existing studies often examine the influence of single variables in isolation, neglecting the differences in particle size distribution, surface characteristics, and reactivity of multi-source solid wastes such as steel slag, tailings sand, and recycled coarse aggregates, and failing to construct a synergistic optimization framework that takes into account density, reaction kinetics, and interfacial mechanics. In this context, simply combining activators and fibers not only fails to achieve a synergistic effect of 1+1>2, but may also lead to secondary problems such as deterioration of workability and decreased volume stability due to mutual interference between components.

[0005] Therefore, how to fully activate the potential cementitious activity of steel slag, and at the same time, construct a method for preparing steel slag concrete that can significantly improve early strength and greatly enhance fracture toughness by precisely controlling the composite activation system, mixed fiber type and multi-solid waste aggregate gradation, and achieve efficient synergistic resource utilization of various industrial solid wastes in the process, has become a key challenge and an urgent technical problem for those skilled in the art. Summary of the Invention

[0006] To achieve the above-mentioned objectives, this invention provides a method for preparing fiber-reinforced steel slag concrete activated by an alkaline activator. This method constructs a concrete system comprising a composite alkaline activator, hybrid fibers, and aggregates from multiple sources of industrial solid waste. This significantly enhances the early strength and fracture toughness of the material while improving the potential cementitious activity of steel slag, and also achieves efficient resource utilization of various industrial solid wastes.

[0007] The preparation method of fiber-reinforced steel slag concrete activated by the alkaline activator includes the following steps: S1, firstly, pre-wetting the steel slag and recycled coarse aggregate; S2, then dissolving the composite alkaline activator in the remaining mixing water to form a uniform solution; S3, then adding cement, tailings sand, and natural sand to the pre-wetted aggregate for preliminary mixing; then adding the composite alkaline activator solution and water-reducing agent to the mixture and stirring, followed by adding corrugated steel fibers and bundled polypropylene fibers and continuing stirring to obtain the mixture; S4, finally vibrating the mixture to form the final product and performing standard curing.

[0008] Specifically, the concrete composition comprises the following components by mass percentage: a cementitious system consisting of 20% to 30% cement and 15% to 25% steel slag that has been heat-treated to eliminate free calcium oxide and free magnesium oxide; an aggregate system consisting of 25% to 35% recycled coarse aggregate, 10% to 20% tailings sand, and 5% to 10% natural sand, with the sum of the mass percentages of each component being 100%; and a composite alkaline activator consisting of water glass with a modulus of 1.0 to 1.5, sodium carbonate, and sodium hydroxide in a mass ratio of 1.5:1. The mixture comprises a 2.5:1 ratio of water glass (based on the total mass of silica and sodium oxide) at 2% to 4% of the steel slag mass, and a 1% to 2% ratio of the mixed alkali at 1% to 2% of the steel slag mass. The hybrid fibers consist of corrugated steel fibers at a volume ratio of 1.0% to 1.5% and bundled polypropylene fibers at a volume ratio of 0.4% to 0.6%. Auxiliary components include water, with a water-cement ratio controlled between 0.4 and 0.5, and a water-reducing agent at a volume ratio of 0.8% to 1.2% of the total mass of the cementitious material. The total water content in the water-cement ratio includes pre-wetting water, mixing water for dissolving the activator, and the water contained in the liquid activator (such as water glass solution).

[0009] Furthermore, in the pre-wetting treatment step, steel slag and recycled coarse aggregate are placed in a mixer. The amount of pre-wetting water is determined according to the 1-hour water absorption rate of the aggregate, which is usually 8%-15% of the total mixing water. The mixing time is 2 minutes to ensure that there is no visible water on the surface of the aggregate after mixing and that the interior is saturated with water, so as to fully wet the surface of the aggregate and eliminate the influence of its water absorption effect on the subsequent hydration reaction.

[0010] In a preferred embodiment of the present invention, the dissolution process of the composite alkaline activator is as follows: water glass, sodium carbonate and sodium hydroxide are added sequentially to 85% to 92% of the total mixing water, and the mixture is stirred continuously at room temperature until it is completely dissolved and the solution is clear and transparent, forming a homogeneous activating solution.

[0011] Further, step S3 specifically includes the following two stages: The first stage involves adding cement, tailings sand, and natural sand to the pre-wetted aggregate and stirring at low speed for 1 minute to initially disperse the dry powder components; the second stage involves introducing the composite alkaline activator solution and water-reducing agent, then adding mixed fibers and stirring at high speed for 2 minutes to ensure uniform fiber distribution and no clumping, while the water-reducing agent fully exerts its dispersing effect to maintain good workability. The low-speed stirring speed is 50 r / min to 70 r / min, and the high-speed stirring speed is 110 r / min to 130 r / min.

[0012] In the molding and curing step, the mixed concrete mixture is poured into a standard mold, compacted using a vibrating table, and demolded after standing for 24 hours. It is then placed in a standard curing environment with a temperature of 20±2℃ and a relative humidity of not less than 95% for a curing period of 28 days or 90 days.

[0013] The steel slag used in this invention undergoes a hot quenching process to reduce the content of free calcium oxide and free magnesium oxide within it to below the safe threshold, preventing structural deterioration due to subsequent volume expansion. The recycled coarse aggregate is obtained from the crushing and screening of waste concrete, with a particle size range of 5mm to 20mm. The tailings sand is a fine-particle byproduct generated during the beneficiation process of metal mines, with a particle size less than 4.75mm. The natural sand is river sand or manufactured sand that meets national standards, used to adjust the continuity of the overall aggregate gradation. For steel slag from different sources (such as electric furnace slag and converter slag), the hot quenching pressure and time should be dynamically adjusted by detecting the free calcium oxide content until f-CaO < 0.5%.

[0014] The water glass modulus in the composite alkaline activator is limited to between 1.0 and 1.5. Within this range, the degree of polymerization of silicate ions is moderate, which can effectively promote the dissolution of the silica-alumina phase in steel slag without causing excessive shrinkage or microcrack concentration due to excessive alkalinity. The mass ratio of sodium carbonate to sodium hydroxide is set between 1.5:1 and 2.5:1. This ratio can synergistically regulate the pH value of the pore liquid and the sodium ion concentration, and optimize the formation rate and micromorphology of CSH gel.

[0015] Among the hybrid fibers, the corrugated steel fibers have a high aspect ratio and surface roughness, which can effectively bridge macroscopic cracks and absorb a large amount of fracture energy; the bundled polypropylene fibers automatically disperse into monofilaments during stirring, filling the micropores of the matrix and inhibiting the development of early plastic shrinkage cracks; the volumetric doping of the two fibers is controlled between 1.0% and 1.5% and 0.4% and 0.6% respectively, which can achieve a multi-scale toughening effect without significantly reducing workability.

[0016] In the aggregate system, recycled coarse aggregate provides the main skeleton support, tailings sand fills the gaps between coarse aggregate as fine aggregate, and natural sand is used to further optimize the particle bulk density. The three together construct a continuous gradation structure, which improves the concrete density by 10% to 15% compared with the traditional single system.

[0017] The water-reducing agent is a polycarboxylate-based high-performance water-reducing agent. Its molecular chain structure contains multiple anchoring groups and sterically hindered branches, which can stably adsorb onto the surface of cementitious material particles in a highly alkaline environment, significantly reducing water consumption and improving fluidity.

[0018] The key to the preparation method described in this invention lies in the synergistic mechanism of the composite alkaline activator, hybrid fibers, and multi-solid waste aggregates: the composite alkaline activator activates the potential active components in steel slag, generating a large amount of dense CSH gel. This gel not only fills the pores and improves the matrix strength, but also coats the fiber surface to form a strongly bonded interface layer, increasing the fiber-matrix interface bonding strength by 15% to 20%. At the same time, the hybrid fibers effectively inhibit the propagation of microcracks through physical bridging and energy dissipation mechanisms, increasing the material toughness index by more than 40%. The optimized aggregate gradation provides suitable spatial constraints for the activation reaction and ensures the uniform distribution of fibers in three-dimensional space.

[0019] The preparation method provided by this invention is fully compatible with existing commercial concrete production line equipment. No new special equipment is required. Industrial production can be achieved simply by adjusting the order of raw material feeding and the mixing time. It has good engineering applicability and promotion prospects.

[0020] In summary, this invention successfully solves the technical challenges of slow early strength development, insufficient toughness, and low co-utilization rate of solid waste in steel slag concrete by systematically integrating composite alkaline activation technology, hybrid fiber reinforcement strategy, and multi-source industrial solid waste aggregate gradation design, achieving a balance between mechanical properties, durability, and environmental benefits. Through the synergistic effect of water glass with a modulus of 1.0–1.5 and a mixed alkali of sodium carbonate / sodium hydroxide, CSH gel generated on the surface of steel slag particles coats the fiber surface, forming a strongly bonded interface layer, thereby increasing the fiber-matrix interfacial bond strength by 15% to 20%. Attached Figure Description

[0021] Figure 1 This is a schematic diagram of the process flow of the steel slag concrete preparation method according to Embodiment 1 of the present invention.

[0022] Figure 2 This is a SEM microstructure image of steel slag concrete in an embodiment of the present invention. Detailed Implementation

[0023] The present invention will be further described below with reference to the accompanying drawings and embodiments, but this is not intended to limit the scope of the invention; it is merely illustrative. It should be noted that, unless otherwise specified, the embodiments and technical features described in this application can be combined with each other. Unless otherwise indicated, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods. Unless otherwise specified, the materials, reagents, etc., used in the following embodiments are commercially available.

[0024] like Figure 1As shown, this invention provides a method for preparing fiber-reinforced steel slag concrete activated by an alkaline activator. The core of this method lies in the synergistic effect of a composite alkaline activator, hybrid fibers, and multi-source industrial solid waste aggregates to construct a concrete system with high early strength, excellent fracture toughness, and good environmental compatibility. The following detailed description of the technical solution of this invention, in conjunction with preferred embodiments, will ensure that those skilled in the art can fully reproduce this invention based on the described content.

[0025] Example 1

[0026] The raw materials used in this embodiment include: ordinary silicate cement (P·O 42.5), converter steel slag after hot quenching treatment, recycled coarse aggregate, tailings sand, natural river sand, water glass solution with a modulus of 1.2, analytical grade sodium carbonate and sodium hydroxide, corrugated steel fibers, bundled polypropylene fibers, and polycarboxylate-based high-performance water-reducing agent. The hot quenching treatment process includes: placing the steel slag in a hot quenching tank, holding it at 120-150℃ for 4-8 hours under a steam pressure of 0.15-0.25 MPa, and then allowing it to cool naturally to room temperature. The steel slag, after hot quenching treatment, has a free calcium oxide content of less than 0.5% and a free magnesium oxide content of less than 1.0%, meeting the safety standards for use. The recycled coarse aggregate is obtained from waste concrete through crushing and screening, with a particle size range of 5 mm to 20 mm and a crushing index value of 18%. The tailings sand comes from a by-product of iron ore beneficiation, with a particle size of less than 4.75 mm and a fineness modulus of 2.3. The fineness modulus of the natural river sand is 2.6. The corrugated steel fiber has a length of 35 mm, a diameter of 0.55 mm, and a tensile strength of not less than 1100 MPa. The bundled polypropylene fiber has a monofilament diameter of 18 μm, a length of 12 mm, and a tensile strength greater than 400 MPa. The water glass solution has a solid content of 38% and a modulus of 1.2. The water-reducing agent has a solid content of 40% and a water reduction rate of ≥25%.

[0027] The concrete composition in this embodiment, by mass percentage, is as follows: 25% cement, 20% hot-quenched steel slag, 25% recycled coarse aggregate, 20% tailings sand, and 10% natural sand (the sum of the mass percentages of each component is 100%); the water glass content is 3% of the steel slag mass, the mixed alkali (sodium carbonate and sodium hydroxide mixed at a mass ratio of 2:1) content is 1.5% of the steel slag mass; the corrugated steel fiber volume content is 1.2%, and the bundled polypropylene fiber volume content is 0.5%; the water-cement ratio is controlled at 0.45; and the water-reducing agent content is 1.0% of the total mass of the cementitious materials (cement + hot-quenched steel slag). The above proportions were determined based on orthogonal experimental optimization results, aiming to balance early strength development, workability, and long-term durability.

[0028] The preparation process strictly follows these steps. First, pre-wetting treatment of the aggregate is carried out: the weighed hot-quenched steel slag and recycled coarse aggregate are put into a forced mixer, and clean water accounting for 10% of the total mixing water is added. The mixture is stirred at low speed (about 60 r / min) for 2 minutes at room temperature to fully wet the surface of the aggregate and achieve a saturated surface-dry state, thereby eliminating the subsequent adsorption effect of the aggregate on the mixing water and avoiding the impact on the uniformity of the activation reaction due to the local reduction of the water-cement ratio caused by internal water absorption.

[0029] Subsequently, a composite alkaline activator solution was prepared: the remaining 90% of the mixing water was poured into a container, and then precisely measured amounts of water glass, sodium carbonate, and sodium hydroxide were added sequentially. Specifically, the liquid water glass and sodium hydroxide were first mixed to adjust the modulus, and sodium carbonate and the remaining mixing water were added after the reaction stabilized to ensure the stability of the activating solution. The solution was continuously stirred with a mechanical stirrer for 15 minutes at room temperature until the solid was completely dissolved, the solution was clear and transparent, and there were no visible particles or precipitates, forming a homogeneous and stable composite activating solution. The pH of this activating solution was approximately 13.2, possessing sufficient alkalinity to activate the aluminosilicate phase in the steel slag.

[0030] Next, the first stage of dry mixing is carried out: the pre-wetted aggregate is retained in the mixer, and cement, tailings sand, and natural sand are added in sequence. The mixer is started and run at low speed (about 60 r / min) for 1 minute to allow the dry powder components to initially disperse and come into contact with the wet aggregate surface, forming a uniform dry-mix system. No liquid is introduced at this stage to avoid premature activation of local reactions that could lead to agglomeration or uneven reaction.

[0031] The second stage, wet mixing and fiber incorporation, then commences: All the prepared composite activating liquid is poured into the mixer, along with a precisely measured amount of polycarboxylate superplasticizer. The mixer is started and initially stirred at low speed for 30 seconds to preliminarily wet the dry mix; then switched to high speed (approximately 120 r / min) for 1 minute to ensure full contact between the activating liquid and the cementitious material and initiate the dissolution reaction. Following this, pre-weighed corrugated steel fibers and bundled polypropylene fibers are slowly added to the mixer in batches, and high-speed mixing continues for 2 minutes. During mixing, the bundled polypropylene fibers automatically unbundle into monofilaments under shear force, dispersing evenly in the slurry; the corrugated steel fibers, due to their corrugated surface structure, exhibit a self-locking effect, effectively preventing sedimentation and clumping. The final mixture exhibits a uniform slurry coating the aggregate, with fibers randomly distributed in three dimensions and no significant bleeding or segregation. The slump is controlled at 160±10 mm, meeting the requirements for pumping construction.

[0032] After mixing, immediately pour the mixture into 40 mm × 40 mm × 160 mm prism molds or 150 mm cube molds. Compact the mixture using a vibrating table at a frequency of 50 Hz for 20 seconds, until a slurry forms on the surface and no obvious air bubbles escape. After molding, cover the specimens with plastic film and place them in a standard curing room at a temperature of 20 ± 2℃ and a relative humidity of not less than 95% for 24 hours. After 24 hours, demold and continue standard curing under the same temperature and humidity conditions until the specified age (e.g., 7 days, 28 days, or 90 days).

[0033] Example 2

[0034] In this embodiment, the steel slag replacement rate is increased to 25%, while the water glass modulus is adjusted to 1.0, the mixed alkali ratio is adjusted to sodium carbonate:sodium hydroxide = 1.5:1, the steel fiber volume content is set to 1.5%, and the polypropylene fiber content is 0.6%. The remaining steps remain the same.

[0035] Comparative Example 1

[0036] Unlike Example 1, this comparative example uses the same aggregate system (25% recycled coarse aggregate, 15% tailings sand, and 10% natural sand), but the cementitious system uses only cement (55%), without steel slag, and without adding any activators or fibers. The water-cement ratio is also 0.45, and the water-reducing agent dosage is 1.0%. The preparation process is the same except for omitting the activator preparation and fiber addition steps. This comparative example represents the typical performance level of traditional recycled aggregate concrete.

[0037] Comparative Example 2

[0038] This comparative example introduces 20% steel slag to replace cement, based on Comparative Example 1, but without applying any alkaline activator or adding fibers. Because the steel slag is not activated, its potential activity cannot be released, resulting in extremely slow early strength development.

[0039] Comparative Example 3

[0040] This comparative example differs from Example 1 by removing the hybrid fibers, while keeping the other components and processes unchanged. This example is used to evaluate the contribution of fibers to toughness.

[0041] Standard specimens were prepared for Example 1 and the three comparative examples, and their 7-day and 28-day compressive strength, 28-day flexural strength, and fracture toughness index (characterized by the area under the load-displacement curve) were tested. The test results are summarized in the table below:

[0042]

[0043] The data show that Example 1 achieved 65% of the 28-day strength (24.8 / 38.2≈65%) in just 7 days, significantly higher than Comparative Example 1's 62% (22.1 / 35.6) and Comparative Example 2's 43% (11.3 / 26.4), demonstrating that the composite alkaline activator effectively accelerated the early reaction kinetics of the steel slag. Simultaneously, the fracture toughness index of Example 1 increased by 89% compared to Comparative Example 1 and by 65% ​​compared to Comparative Example 3, indicating that the hybrid fiber system achieved a significant multi-scale toughening effect. It is noteworthy that although Comparative Example 3 contained no fibers, it generated a dense CSH gel due to the activation effect, and its flexural strength was still superior to Comparative Example 1, indicating that the activation reaction itself can also improve the matrix brittleness.

[0044] Example 2 adjusted some parameters to verify the system's adaptability. The fluidity of the mixture decreased slightly under this ratio, but it could be restored to a workable state by fine-tuning the water-reducing agent dosage to 1.2%. After 28 days of curing, the compressive strength still reached above the design strength grade C40, indicating that the system of this invention has good parameter tolerance. The 7-day compressive strength of Example 2 was slightly lower than that of Example 1, mainly due to the increased steel slag replacement rate to 25%, which slightly slowed the early hydration reaction rate; however, this was partially compensated for by increasing the fiber content. The 28-day compressive strength was close to that of Example 1, indicating that the composite alkaline activator could still effectively activate the potential activity of the high-replacement-rate steel slag. The 28-day flexural strength was slightly higher than that of Example 1, thanks to the increased steel fiber volume content enhancing the matrix's flexural toughness. The fracture toughness index was significantly higher than that of Example 1, confirming the synergistic effect of increased total fiber content on multi-scale crack control.

[0045] Furthermore, the fiber-matrix interface pull-out strength of the concrete prepared in Example 1 was tested using a single-fiber pull-out test method with a loading rate of 0.5 mm / min. The results showed that the steel fiber-matrix interface pull-out strength in this example was 3.2 MPa, and the polypropylene fiber-matrix interface pull-out strength was 1.8 MPa. In the un-activated, unreinforced control group, the steel fiber-matrix interface pull-out strength was 2.7 MPa, and the polypropylene fiber-matrix interface pull-out strength was 1.5 MPa. The fiber-matrix interface bond strength in this example was approximately 18.5% (steel fiber) and 20% (polypropylene fiber) higher than the control group, verifying the effect of the composite activation system on improving interface bond strength. The optimal implementation parameters determined through orthogonal experiments were: water glass modulus 1.2, steel fiber volume fraction 1.2%, polypropylene fiber volume fraction 0.5%, and steel slag replacement rate 20%. Under these conditions, the 7-day compressive strength of the concrete reached 65% of the 28-day strength, significantly better than the 30% to 40% level of the un-activated, unreinforced control group.

[0046] Furthermore, such as Figure 2As shown, scanning electron microscopy (SEM) observation of the fracture morphology of the example at 28 days showed that the surface of the steel slag particles was coated with a large amount of amorphous CSH gel. The gel structure was dense and tightly bound to the unreacted nuclei. There were obvious mechanical interlocking marks at the interface between the corrugated steel fibers and the matrix. The thickness of the interfacial transition zone (ITZ) was less than 30 μm, with no obvious pores or microcracks. The polypropylene monofilament fibers were uniformly embedded in the matrix, and the surrounding slurry was continuous, with no debonding observed. Energy dispersive spectroscopy (EDS) analysis showed that the calcium-to-silicon ratio (Ca / Si) in the interfacial region was approximately 1.6, close to the ideal tobermorite structure, indicating that the activated reaction generated high-quality hydration products.

[0047] Furthermore, X-ray diffraction (XRD) patterns showed that the intensity of characteristic peaks (such as RO phase and C2S) in the steel slag of the example decreased significantly after 28 days, while obvious CSH broadening peaks and a small amount of calcium aluminate hydrate (AFm) diffraction peaks appeared, confirming that the silicon and aluminum components in the steel slag had effectively participated in the reaction. In contrast, the characteristic peaks of the steel slag in Comparative Example 2 remained almost unchanged, indicating that its activity was difficult to release without excitation.

[0048] Regarding process adaptability, the method described in this invention is fully compatible with existing commercial concrete mixing plant equipment. In actual production, only the following adjustment is needed in the feeding sequence: first, recycled coarse aggregate and steel slag are added to the mixing host for pre-wetting; then, sand materials are added for dry mixing; next, pre-prepared activating liquid and water-reducing agent are pumped in; finally, fibers are added in batches. The entire mixing cycle is controlled within 6 minutes, consistent with the production cycle of conventional concrete, without the need for equipment modification or the addition of a dedicated fiber dispersion device.

[0049] Regarding the mechanism of action of composite alkaline activators, in the water glass modulus range of 1.0 to 1.5, silicate ions exist in an oligomeric state (such as SiO4). 4- Si2O7 6- It is mainly composed of α, which has high reactivity and can quickly react with Ca in steel slag. 2+ Al 3+ Plasma complexation promotes the depolymerization of the glass phase; sodium carbonate provides Na. + Maintaining high ionic strength inhibits excessive silicate polymerization, while CO3 2- Can be used with Ca 2+ The process generates calcite microcrystals that fill the micropores; sodium hydroxide rapidly raises the pH of the system to above 13, disrupting the passivation film on the steel slag surface and accelerating the dissolution of silicon and aluminum. The synergistic effect of these three agents maximizes the activation efficiency and avoids the risks of intense exothermic reactions and shrinkage cracking caused by using a single strong alkali (such as pure NaOH).

[0050] The synergistic toughening mechanism of hybrid fibers is manifested at multiple scales: the corrugated steel fibers have an aspect ratio of approximately 64 and a surface corrugation depth of 0.15 mm, dissipating a large amount of energy through pull-out and bridging effects when macroscopic cracks form; the bundled polypropylene fibers, after unbundling, have a single filament aspect ratio of approximately 670, effectively inhibiting the initiation and propagation of microcracks smaller than 0.1 mm, especially preventing surface cracking caused by moisture evaporation during the plastic stage. Extensive experimental verification has shown that the combination of 1.0%–1.5% steel fiber and 0.4%–0.6% polypropylene fiber achieves optimal toughness improvement while ensuring a slump of no less than 150 mm.

[0051] In terms of aggregate gradation design, the mass ratio of recycled coarse aggregate, tailings sand and natural sand was optimized using Fuller curves, resulting in an overall bulk density of 2380 kg / m³. 3 Compared to using natural aggregate alone, it improves efficiency by about 12%. Close packing not only reduces the amount of cementitious material used, but also provides a confined space to stimulate the reaction, which is conducive to the directional growth of CSH gel in the pores and the formation of a denser microstructure.

[0052] In summary, this invention constructs a highly synergistic multiphase composite system by precisely controlling the raw material composition, activator formulation, fiber type and dosage, aggregate gradation, and mixing process parameters. This system exhibits excellent comprehensive performance in engineering practice: rapid early strength development, stable later-stage strength growth, significantly improved fracture toughness, and controllable workability. Furthermore, it achieves efficient synergistic utilization of various industrial solid wastes such as steel slag, recycled aggregates, and tailings, aligning with the development direction of green and low-carbon building materials. All technical details have been fully disclosed, and those skilled in the art can directly implement this embodiment without creative effort to achieve the desired technical effects.

[0053] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.

Claims

1. A method for producing an alkali-activated fiber reinforced steel slag concrete, characterized by, The method comprises the following steps: S1, pre-wetting the steel slag and recycled coarse aggregate with mixing water to obtain a mixed aggregate; S2, dissolving water glass, sodium carbonate and sodium hydroxide in mixing water to form a composite alkaline activator solution; S3, adding cement, tailings sand and natural sand to the mixed aggregate for preliminary dry mixing, then adding the composite alkaline activator solution and water reducing agent for stirring, and then adding corrugated steel fibers and bundle-shaped polypropylene fibers for continuous stirring to obtain a mixture; S4, vibrating and forming the mixture to obtain steel slag concrete; The steel slag concrete comprises, by mass percentage based on the total mass, 20-30% of cement, 15-25% of steel slag, 25-35% of recycled coarse aggregate, 10-20% of tailings sand, and 5-10% of natural sand, and the sum of the mass percentages of the components is 100%. The water glass content is 2-4% of the mass of the steel slag, and the sodium carbonate and sodium hydroxide are mixed at a mass ratio of 1.5:1 to 2.5:1, and the total content is 1-2% of the mass of the steel slag. The corrugated steel fibers and the bundle-shaped polypropylene fibers are externally added, and the volume content of the corrugated steel fibers is 1.0-1.5% of the total volume of the steel slag concrete, and the volume content of the bundle-shaped polypropylene fibers is 0.4-0.6% of the total volume of the steel slag concrete. The cement and the steel slag form a cementitious material, the water-binder ratio of which is 0.4-0.5, and the water reducing agent content is 0.8-1.2% of the total mass of the cementitious material.

2. The production method according to claim 1, characterized by, In the pre-wetting process, 8-15% of the total mixing water is added to the steel slag and recycled coarse aggregate, and the aggregate is stirred at room temperature for 2 minutes to achieve a saturated surface-dry state.

3. The method of claim 1, wherein, The preparation method of the composite alkaline activator solution comprises: adding water glass, sodium carbonate and sodium hydroxide into 85-92% of the total mixing water, and stirring at room temperature until the solution is completely dissolved and clear.

4. The method of claim 1, wherein, S3 specifically comprises the following two stages: the first stage is to add cement, tailings sand and natural sand to the mixed aggregate for low-speed stirring for 1 minute; the second stage is to add the composite alkaline activator solution and water reducing agent for low-speed stirring for 30 seconds and then high-speed stirring for 1 minute, and then add corrugated steel fibers and bundle-shaped polypropylene fibers for continuous high-speed stirring for 2 minutes to make the fibers uniformly dispersed and not clustered; the low-speed stirring speed is 50-70 r / min, and the high-speed stirring speed is 110-130 r / min.

5. The preparation method according to claim 1, characterized in that, The modulus of the water glass is 1.0-1.

5.

6. The method of claim 1, wherein, The particle size of the recycled coarse aggregate is 5-20 mm, the particle size of the tailings sand is less than 4.75 mm, and the natural sand is river sand or machine-made sand.

7. The preparation method according to claim 1, characterized in that, The water reducing agent is a polycarboxylic acid high-performance water reducing agent.

8. The method of claim 1, wherein, The length of the corrugated steel fibers is 30-40 mm, and the diameter is 0.5-0.6 mm; the single-fiber diameter of the bundle-shaped polypropylene fibers is 15-20 μm, and the length is 10-15 mm.

9. The method of claim 1, wherein, The standard curing conditions are a temperature of 20±2℃ and a relative humidity of not less than 95%.

Citation Information

Patent Citations

  • Slag-coal ash compound solid exciter and preparation method thereof

    CN102627426A

  • Steel-PVA hybrid fiber recycled brick aggregate concrete and preparation method thereof

    CN110078446A

  • Alkali-activated gelling composition, slag material and application thereof

    CN118637844A

  • Preparation method of steel slag reinforced composite alkali-activated geopolymer

    CN119912184A

  • Low-carbon premixed concrete based on industrial solid waste synergistic activation and preparation method thereof

    CN120309286A